The rise of crowdsourcing using social media platforms: Security and privacy issues - Hassan N.H.; Rahim F.A. (Universiti Putra Malaysia Press, 2023)
The increasing adoption of social media is a viable means in crowdsourcing. It can facilitate the connectivity of collaboration between different organisations, people and society to produce innovative and cost-effective solutions to many problems. Social media have opened up unprecedented new possibilities of engaging the public in meaningful ways through crowdsourcing. However, the growing number of security and privacy issues in social media may weaken the efficacy of crowdsourcing. This study aims to provide a basic understanding of security and privacy issues in line with the growth of crowdsourcing using social media platforms. This study also illustrates how crowdsourcing and social media data can lead to security and privacy issues in different environments. Lastly, this study proposes future works that may serve as direction for scholars to explore security and privacy in crowdsourcing through social media platforms. Secondary sources obtained from journals, conference papers, industry reports and books were reviewed to gather information. 2017 Universiti Putra Malaysia Press.